Dexmedetomidine for sedation following cerebral angiography - Taghon, Thomas; Rabe, Andrew J.; Tobias, Joseph D. (Journal of Pediatric Neurology, 2011)
Dexmedetomidine, a centrally acting α2-adrenergic agonist, is being used with increased frequency in the pediatric population due to its unique ability to render patients in a sedated, yet cooperative state, with a limited risk of adverse respiratory or hemodynamic effects. We report the successful use of dexmedetomidine to provide sedation following general anesthesia in two adolescents following cerebral angiography. Dexmedetomidine was used with limited effects on hemodynamic and ventilatory function to provide sedation and limit movement to prevent hematoma formation at the femoral artery cannulation site. Both patients had underlying neurobehavioral disorders, which precluded their ability to cooperate with a prolonged period of post-procedure immobility. The potential application of dexmedetomidine in this unique patient population is discussed.
Keywords: Dexmedetomidine; procedural sedation; cerebral angiography